2014
DOI: 10.1016/j.bpc.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent energetics of calmodulin domain interactions with regulatory regions of the Ryanodine Receptor Type 1 (RyR1)

Abstract: Calmodulin (CaM) plays a vital role in calcium homeostasis by allosterically modulating intracellular calcium channels including the homo-tetrameric human Ryanodine Receptor Type 1 (hRyR1). Apo (calcium-free) CaM activates hRyR1 while calcium-saturated CaM inhibits it. Two CaM-binding regions (residues 1975–1999 and 3614–3643) identified in each RyR1 monomer were proposed to allow CaM to bridge adjacent RyR1 subunits. We explored the distinct roles of CaM domains by using fluorescence anisotropy to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 75 publications
(117 reference statements)
2
9
0
Order By: Relevance
“…CaM binding properties of the RyRs have focused on RyR1. It has been reported that apoCaM and Ca 2þ -CaM bind with nanomolar affinity (similar to that of the full-length channel) to a synthetic peptide matching amino acids 3614-3643 of RyR1 (RyRp) (11,12), while other studies suggest that the affinity is much lower (micromolar) in the apo-state (13,14). In this article, the position number in the 31-residue RyRp starts from 1 at the N-terminus (3614 in full-length receptor) to 31 at the C-terminus (RyRp sequence in Materials and Methods).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…CaM binding properties of the RyRs have focused on RyR1. It has been reported that apoCaM and Ca 2þ -CaM bind with nanomolar affinity (similar to that of the full-length channel) to a synthetic peptide matching amino acids 3614-3643 of RyR1 (RyRp) (11,12), while other studies suggest that the affinity is much lower (micromolar) in the apo-state (13,14). In this article, the position number in the 31-residue RyRp starts from 1 at the N-terminus (3614 in full-length receptor) to 31 at the C-terminus (RyRp sequence in Materials and Methods).…”
Section: Introductionmentioning
confidence: 98%
“…Trypsin cleavage, alkylation (11), and site-directed mutagenesis (16) suggested that apoCaM and Ca 2þ -CaM bind to the same RyR1 region that includes Cys 22 (17) and Leu 11 in RyRp (16). A recent fluorescence anisotropy study proposed a model in which the C-domain of CaM is bound to the RyRp site in the presence and absence of Ca 2þ , but the N-domain of CaM is bound only in the presence of Ca 2þ (13). There is currently limited information on the structure and dynamics of the isolated RyRp, the apoCaM/RyRp complex, and the Ca 2þ -CaM/ RyRp complex in solution.…”
Section: Introductionmentioning
confidence: 99%
“…Ca 2+ binds to the regulatory protein troponin-C, which causes a conformational shift of the tropomyosin from myosin binding sites on the actin molecule (Frontera & Ochala, 2015;Rebbeck et al, 2014) ii. Ca 2+ plays a role in myosin phosphorylation and conformational activation of calmodulin Newman, Sorensen, Kilpatrick, & Shea, 2014;Rebbeck et al, 2014). This myogenic mechanism will be further discussed later in this review.…”
Section: Muscle Contraction Physiologymentioning
confidence: 98%
“…The ELCs are located closer to the N-terminal, acting as a stabilization mechanism for the N-terminal of the myosin molecule, and the RLCs are the phosphorylatable light chains, located closer to the filamentous backbone of the myosin molecule ( Figure 2); (Gardiner, 2001). Specific enzymes enable conformational alterations of the positioning of the myosin N-terminal during prolonged bouts of muscular activation Midde et al, 2013;Newman et al, 2014). Figure 2: Ca2+ / CaM interaction with MLCK, shows the conformational shift in CaM when the Ca 2+ -binding sites are occupied by Ca 2+ .…”
Section: Myogenic Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation